Role of the industrial microorganisms collection in innovative development of the processing and food industry (Experimental biology, 2015)
The structure and activity of industrial cultures collection of KAZNIIPPP is shown. Compositions of lactic acidbacteria and yeast for production of biological preparations and sour-milk products are described.
Keywords: сollection; depositary; strains; cultures; storage; lactic acid bacteria; yeast; consortium; biological preparations; starters; stability